Comparison of three different stents for endoscopic ultrasound‐guided drainage of pancreatic fluid collection: A large retrospective study. Issue 4 (21st January 2019) - Wang, Zhijie; Zhao, Shengbing; Meng, Qianqian; Wang, Shuling; Chen, Yan; Wang, Fuming; Li, Qiang; Yao, Jun; Du, Yiqi; Jin, Zhendong; Bai, Yu; Li, Zhaoshen; et al.
Abstract: Background and Aim: Endoscopic transmural drainage has been recognized as the first‐line treatment for pancreatic fluid collection (PFC). Currently, three different types of stents have been extensively applied, including double pigtail plastic stent (PS), fully covered self‐expanding metal stent (FCSEMS), and novel lumen‐apposing metal stent (LAMS). Nonetheless, limited data are available about the comparison among them in terms of their clinical outcomes and safety for endoscopic ultrasound‐guided drainage of PFC. Methods: The current retrospective study was carried on 160 PFC patients undergoing endoscopic ultrasound‐guided drainage from 2010 to 2018 at a single tertiary care center. Patients were divided into three groups based on different drainage ways: drainage using PS, FCSEMS, or LAMS. Results: A total of 160 PFC patients (104 male and 56 female) were analyzed in this retrospective study, including 62 patients drained with PS, 28 with FCSEMS, and 70 with LAMS. Typically, the technical success (93.5% vs 96.4% vs 94.3%, P = 1.000) and treatment success rates (84.6% vs 85.2% vs 89.2%, P = 0.763) were similar between PS, FCSEMS, and LAMS. With regard to major adverse events, four patients (FCSEMS: n = 2 and LAMS: n = 2) with pseudoaneurysms developed severe bleeding; among them, 75% (3/4) of patients were observed within 2 weeks after intervention, and two patients in LAMS group died. Conclusions: There are no significant differences in the clinical outcomes of PFC patients treated with PS, FCSEMS, or LAMS. Nonetheless, severe (or even fatal) bleeding may occur at the early stage after metal stent placement, which should be paid particular attention to.